Proteolytic cleavage of Beclin 1 exacerbates neurodegeneration - Bieri, Gregor (Mol Neurodegener, 2018)
BACKGROUND: Neuronal cell loss contributes to the pathology of acute and chronic neurodegenerative diseases, including Alzheimer’s disease (AD). It remains crucial to identify molecular mechanisms sensitizing neurons to various insults and cell death. To date, the multifunctional, autophagy-related protein Beclin 1 has been shown to be both necessary and sufficient for neuronal integrity in neurodegenerative models associated with protein aggregation. Interestingly, besides its role in cellular homeostasis, Beclin 1 has also been ascribed a role in apoptosis. This makes it critical to elucidate whether Beclin 1 regulates neuronal death and survival across neurodegenerative conditions independent of protein clearance. Here, we provide experimental evidence for a direct functional link between proteolytic cleavage of Beclin 1 and apoptotic neuronal cell loss in two independent models of neurodegeneration in vivo. METHODS: Proteolytic cleavage of Beclin 1 was characterized in lysates of human AD brain samples. We developed viral tools allowing for the selective neuronal expression of the various Beclin 1 forms, including Beclin 1 cleavage products as well as a cleavage-resistant form. The effect of these Beclin 1 forms on survival and integrity of neurons was examined in models of acute and chronic neurodegeneration in vitro and in vivo. Markers of neuronal integrity, neurodegeneration and inflammation were further assessed in a Kainic acid-based mouse model of acute excitotoxic neurodegeneration and in a hAPP-transgenic mouse model of AD following perturbation of Beclin 1 in the susceptible CA1 region of the hippocampus. RESULTS: We find a significant increase in caspase-mediated Beclin 1 cleavage fragments in brain lysates of human AD patients and mimic this phenotype in vivo using both an excitotoxic and hAPP-transgenic mouse model of neurodegeneration. Surprisingly, overexpression of the C-terminal cleavage-fragment exacerbated neurodegeneration in two distinct models of degeneration. Local inhibition of caspase activity ameliorated neurodegeneration after excitotoxic insult and prevented Beclin 1 cleavage. Furthermore, overexpression of a cleavage-resistant form of Beclin 1 in hippocampal neurons conferred neuroprotection against excitotoxic and Amyloid beta-associated insults in vivo. CONCLUSIONS: Together, these findings indicate that the cleavage state of Beclin 1 determines its functional involvement in both neurodegeneration and neuroprotection. Hence, manipulating the cleavage state of Beclin 1 may represent a therapeutic strategy for preventing neuronal cell loss across multiple forms of neurodegeneration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13024-018-0302-4) contains supplementary material, which is available to authorized users.